Financial Plumbing and Monetary Policy - Singh, Manmohan (IMF Working Papers; Working Paper ;, 2014)
This paper focuses on how changes in financial plumbing of the markets may impact the monetary policy options as central banks contemplate lift off from zero lower bound (ZLB). Under the proposed regulations, banks will face leverage ratio constraints. As a result of quantitative easing (QE), banks want balance sheet 'space' for financial intermediation/ non-depository activities. At the same time, regulatory changes are boosting demand for high quality liquid assets. The paper also discusses the role of repo markets and the importance of collateral velocity and the need to avoid wedges between repo and monetary policy rates when leaving ZLB.